John L. Sorenson y Martin H. Raish (comps.). Pre-Columbian Contact with the Americas across the oceans, An Annotated Bibliography. Provo, Utah: Research Press, 1990, 2 vols. no paginados. - Maeth Ch., Russell (Estudios de Asia y África, 1992)
-